“Ye Shall Know Them by Their Fruits” A Mixed Methods Study on Corruption, Competitiveness, and Christianity in Europe and the Americas - García Portilla, Jason (Contributions to Economics, 2022)
XXXVI, 407 p. 38 illus., 36 illus. in color.